Assisting The Formation of English Club Extracurricular Activities at Garuda Junior High School - Syifa Fadhilah Hamid; Isnaniah; Agus Mulyana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Based on the results of the observation of need analysis on students of Garuda Junior High School Tangerang, it shows that students' interest in learning English in class is very minimal and their English skills such as Speaking, Reading, Writing, Listening are still relatively low. The result of the questionnaire shows that students need to learn English not only inside the classroom but also outside the classroom to encounter the lack of their understanding towards English lesson. Online learning during the pandemic also has an impact on students, so that they find it difficult to understand the materials provided by the teacher. Thus, learning English does not run smoothly. Therefore, based on the problems mentioned above, the lecturers of English Departement of Faculty of Education and Teacher Training, Syekh Yusuf Islamic University (UNIS) were intended to provide assistance in the formation of English Club activities to improve students' English skills at SMP Garuda Tangerang. The facilitators used a combination theory and application methods. In general, this activity was carried out through three stages (1) the planning stage (plan), (2) the implementation stage (do), and (3) the reflection stage. The educative workshop and training on the formation of English Club was held at SMP Garuda Tangerang. The workshop are very helpful for the school to actually know about the concept of English Club extracurricular. And, the students also gave positive responses towards the activity and seemed interested in joining the English Club extracurricular.